2007
DOI: 10.1021/ic700381n
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium(V) Oxo Complexes with Acetylacetone Derived Schiff Bases:  Structure and Catalytic Epoxidation

Abstract: Substitution reactions of rhenium(V) oxo precursors [ReOCl3(PPh3)2] or [NBu4][ReOCl4] with the bidentate acetylacetone-derived ketoamine ligands APOH = 4-anilino-3-penten-2-one, DPOH = 4-[2,6-dimethylanilino]-3-penten-2-one, and MTPOH = 4-[2-(methylthio)anilino]-3-penten-2-one gave the complexes [ReO(APO)Cl2(PPh3)] (1), [ReO(DPO)Cl2(PPh3)] (2), and [NBu4][ReOLCl3] (3, L = APO; 4, L = DPO; 5, L = MTPO), respectively. All complexes exhibit only one ketoamino chelate, independent of the amount of ligand added to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 57 publications
7
42
1
Order By: Relevance
“…Molecular views are shown in Figure 1, crystallographic data are presented in Table 2, and selected bond lengths and angles are given in Table 1 The trans coordination of the ligand oxygen atom towards the oxygen atom attached to the rhenium atom is well documented in the literature. [7,18,[40][41][42] For distorted octahedral Re V O complexes with oxygen-containing bidentate ligands, it is suggested that O-Re=O corresponds to a minimum of trans weakening caused by the Re=O multiple bond. In addition, the repulsion exerted by the Re=O atom causes a compression field that tends to increase the mean O=Re-L cis angle beyond 90°.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular views are shown in Figure 1, crystallographic data are presented in Table 2, and selected bond lengths and angles are given in Table 1 The trans coordination of the ligand oxygen atom towards the oxygen atom attached to the rhenium atom is well documented in the literature. [7,18,[40][41][42] For distorted octahedral Re V O complexes with oxygen-containing bidentate ligands, it is suggested that O-Re=O corresponds to a minimum of trans weakening caused by the Re=O multiple bond. In addition, the repulsion exerted by the Re=O atom causes a compression field that tends to increase the mean O=Re-L cis angle beyond 90°.…”
Section: Introductionmentioning
confidence: 99%
“…The equatorial plane of the complexes consists of the two halide atoms, the nitrogen atom, and the chalcogen atom (compounds 1, 2, 9) or an additional nitrogen atom (compound 11) from the ligand. All complexes gave bond lengths for Re=O [18,20,44] In complex 1, the chlorine atoms Cl(1) and Cl(2) are coordinated in cis position to each other with comparable bond lengths of Re (1) …”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases can coordinate many metal ions to form mononuclear or multinuclear complexes because of strong coordination ability and versatile coordination mode of the -C=N-group [1][2][3]. However, only limited Schiff bases of ketone and their complexes have been reported up to now [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Schiff bases have been widely introduced to construct the metal organic framework owing to their various coordination modes [1,2]. The title mononuclear Cu(II) complex is composed of one copper(II) ion and two Schiff base ligands.…”
Section: Discussionmentioning
confidence: 99%